x → 0 lim x 4 1 − x 2 − 4 1 − 4 x 2 + x 4 = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Not an elegant method.
Log in to reply
I know there are some methods more elegant but I have chosen to write that just because I really like Taylor :)
Problem Loading...
Note Loading...
Set Loading...
We have that: 4 1 − 4 x 2 + x 4 = 1 + 4 1 ( − 4 x 2 + x 4 ) + 2 ! 4 1 ( 4 1 − 1 ) ( − 4 x 2 + x 4 ) 2 + 3 ! 4 1 ( 4 1 − 1 ) ( 4 1 − 2 ) ( − 4 x 2 + x 4 ) 3 + 4 ! 4 1 ( 4 1 − 1 ) ( 4 1 − 2 ) ( 4 1 − 3 ) ( − 4 x 2 + x 4 ) 4 + o ( x 4 ) = 1 − x 2 − 4 5 x 4 + o ( x 4 )
Thus: lim x → 0 x 4 1 − x 2 − 4 1 − 4 x 2 + x 4 = lim x → 0 x 4 1 − x 2 − ( 1 − x 2 − 4 5 x 4 ) + o ( x 4 ) = 4 5 = 1 . 2 5